Design Analysis Achievement Target Database Information System at SEAMEO RECFON - Dodi Suswandi; Ivan Hanfi; Widodo Widodo (Journal of Social Research, 2023)
SEAMEO Regional Center for Food and Nutrition (RECFON), is an organization of Southeast Asian Ministers of Education in the field of food and nutrition. The activities carried out by SEAMEO RECFON already have a fairly good system, but there are several problems SEAMEO RECFON actively conducts education, research, training, and community empowerment activities so the need for up-to-date information on food and nutrition topics and services and facilities support all these activities is very important. This important task must be supported by adequate facilities, including the procurement of data processing and communication devices capable of supporting RECFON's activities. For this reason, the author takes the title "Analysis and Design of the Target Achievement Database Information System System at SEAMEO RECFON " This SI / IT strategic planning is made using the Ward and Peppard framework with several analysis methods, namely value chain analysis, by mapping what are the main and supporter activities at SEAMEO RECFON and analyzing the problems of each activity. To see the strengths, weaknesses, opportunities, and threats, a SWOT (Strength, Weakness, Opportunity, Thread) analysis is used. Factors that are successful and can solve problems and needs are used in CSFs (Critical Success Factors) analysis. McFarlan Strategic Grid analysis is used to map existing applications in DPPKA Kampar based on categories, namely support, Key Operational, Strategic, and High Potential. The results achieved through this analysis method are recommendations in the form of 19 information systems, 10 information technologies, and 4 SI and IT management. The information system and information technology are made in the form of a roadmap that will be implemented over the next 3 years by SEAMEO RECFON